Digital Door Lock System Using Arduino and Bluetooth Module (International Journal of Food and Nutritional Sciences, 2021)
The aim of this project is to provide the security. Now a days security system is must for every organization. Access control system is one system that is used for security purpose in many organizations. The main aim of this project is to provide access only if the password of particular user is matched and the access is denied to unauthorized persons. These kinds of doors with secret code locking systems are quite useful for the security purposes. Many departments like Defense, military areas, Research canters, bank security and security for important documents Industries, go-downs, etc can adopt this type where high level security is essential. The same system can be used even at domestic side also; the main advantage of this system is that only authorized persons can operate these doors. This system has intelligence of allowing only valid password. A password in the form of four digits code is offered to the operator, if the correct code is entered through the keyboard of the Bluetooth, then the door will be opened automatically. If the password is wrong, then a message is sent to the authorized mobile through the Bluetooth and buzzer is also activated. It also has the push buttons mechanism through which the user can enter the correct pattern using the push buttons ,if it is correct password then the door opens else a message is sent to the device which is in range of Bluetooth module(HC05) and also the buzzer gets activated.